Implementasi Algoritma Apriori Untuk Menentukan Strategi Pemasaran - Bilqis Ismail Putri, Tiara; Sujatmiko, Bambang; Andriani, Anita (Inovate, 2022)
Store X is retail that provide a variety of toys for girls and boys. Every day the sales transaction data Store X will definitely increase and accumulate. So that data does not accumulate it is good can be used to know the habits of the buyer or of buyer behavior of goods purchased. How to search the goods sold simultaneously can use the data mining methods, which is a technique to analyze large-sized data by finding relationships among the data or the search combination and rule. The search for a combination is done with the process of merging (join) and pruning (prune) items called apriori algorithm. This research resulted in a website-based system by testing data sales transactions as many as 30 data a memorandum of the transaction with a minimum support of 35% and minimum confidence of 75%. So as to form one rule, namely, if buy a Meja Belajar K then will buy a Kreatif Block Tas with the value of the support 36.67% and the value of the confidence 78.57%. Keywords : Association, Apriori Algorithm, The Transaction Data, Sales